Molecular screening for Neisseria gonorrhoeae antimicrobial resistance markers in Nigerian men who have sex with men and transgender women. (November 2018) - Hardick, Justin; Crowell, Trevor A; Lombardi, Kara; Akintunde, Akindiran; Odeyemi, Sunday; Ivo, Andrew; Eluwa, George; Njab, Jean; Baral, Stefan D; Nowak, Rebecca G; Quinn, Thomas C; Barbian, Kent; et al.
Antimicrobial-resistant Neisseria gonorrhoeae (NG) is a global public health issue that threatens effectiveness of current treatments of NG. Increased use of nucleic acid amplification tests (NAATs) in lieu of cultures makes obtaining clinical isolates for susceptibility testing difficult and samples collected in commercial transport buffer for NAATs do not preserve viable organism, while molecular methods of assessing antibiotic susceptibility do not require viable organism. We evaluated 243 NG-positive samples in Aptima transport media including urine, oral, and rectal swabs from Nigerian men who have sex with men for markers to penicillinase-producing NG, ciprofloxacin ( GyrA and ParC mutations), and extended spectrum cephalosporins (ESCs, PenA mosaic [allele X], PonA, mtrR, PorB mutations) by real-time PCR. NG DNA was recovered in 75% (183/243) of samples. Of these, 93% (171/183) were positive for at least one resistance marker. We observed a prevalence of dual resistance markers to penicillin and ciprofloxacin at 46.2% (79/171). Six percent of samples (10/171) tested positive for the PenA mosaic (allele X) ESC marker. These data indicate that antibiotic-resistant NG is common in Nigeria. Laboratory and clinical capacity building in Nigeria should include development of methods to culture NG and determine antimicrobial susceptibility.